Dexrazoxane preferentially mitigates doxorubicin cardiotoxicity in female children with sarcoma - Hari K Narayan; Mary E Putt; Nikitha Kosaraju; Alejandro Paz; Shivani Bhatt; Theodore Plappert; Laura Mercer-Rosa; Saro H Armenian; Ami V Desai; Richard B Womer; Bonnie Ky (Open Heart)
Objective We sought to determine how sex and dexrazoxane therapy influence cardiac remodelling in children with sarcoma receiving high-dose doxorubicin.Methods In a retrospective cohort of 85 children with sarcoma receiving high-dose doxorubicin, echocardiography measures prior to, early after (within 6 months of doxorubicin completion) and 1 – 2 years after doxorubicin completion were quantified. At each follow-up visit, multivariable, propensity-adjusted linear regression models evaluated dexrazoxane’s effects on changes in left ventricular (LV) shortening fraction (SF), structure, strain and wall stress for subgroups divided by sex. Likelihood ratio tests assessed the interaction between sex and dexrazoxane in determining these changes.Results Early after doxorubicin completion, males not treated with dexrazoxane (n = 15) developed increased cavity size and diminished circumferential strain; females (n = 8) developed diminished SF and strain indices, and increased cavity size and wall stress. With dexrazoxane, males (n = 33) demonstrated less deterioration in circumferential strain by 3.4% (95% CI 0.01 to 6.8), and females (n = 29) demonstrated less reduction in SF by 5.7% (95% CI 2.1 to 9.3), and had mitigation of increases in cavity size and wall stress. In interaction analyses, females had greater protection with dexrazoxane with regard to SF (p = 0.019) and cavity size in diastole (p = 0.002) and systole (p ≤ 0.001). These findings largely persisted 1 – 2 years after doxorubicin therapy.Conclusions Early, sustained alterations in LV structure and function occur in children with sarcoma after high-dose doxorubicin, with adverse changes and protective effects of dexrazoxane more pronounced in females as compared with males. Dexrazoxane may have sex-specific cardioprotective effects.